Prova digital, ônus da prova e o protagonismo judicial no processo do trabalho - Rodovalho, Décio Umberto Matoso (2023)
The transformations that the world is experiencing due to the development of information technology and massive use of the internet and the means of collecting, transiting and storing data, have repercussions on everyday forensics and demand the improvement of the evidentiary technique for the prosecution of justice from the perspective of the protection of rights and the constitutional right to process and jurisdiction aimed at implementing fundamental guarantees. This research work aims, based on the theory of evidence, both classical and contemporary, and the basis of European GRPD and LGPD regulation and the national legal system, especially the Federal Constitution and the normative guidelines that govern the Process judicial and particu-larly labor litigation, study the impact of digital evidence in the process and its usefulness for procedural instruction with a view to improving jurisdiction and reducing judicial error in the face of the protection of privacy and the protection of access to personal data sensitive. The idea developed throughout the work was to produce a doctrinal review on the topic. The study will be based on ideas and assumptions. The research was qualitative in nature and aimed to evaluate the best judicial option for regulating the decision on evidence, using the deductive scientific method. The references do not intend to be exhaustive to the point of exhausting the topic, but only to provide a minimum theoretical framework to guide judicial decisions in the face of new technologies, in order to investigate the judicial role in the formation of procedural evidentiary content in the face of the right to privacy and intimacy.